Confabulation of things past in Ian McEwan’s black dogs - Seyed Javad Habibi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Confabulation is a result of memory impairment and a confabulator in many different ways produces various unreliable narratives: either by weaving a detailed narrative to fill in the gaps in his memory or by falsifying his memory due to the absence of deceitfulness occurring in clear consciousness. Concentrating on the unreliability of memory-oriented narrative, particularly, in the narratives with historiographical framework such as Ian McEwan’s novel Black Dogs (1992), this article underlines various types of discrepancies among the major characters’ narratives and lays bare how the memory-based narrative of the novel is crystallized from “the reconstructive theory of memory.” Indeed, the object of this study is to substantiate that those inconstancies and contradictions throw doubt on the central incident of the novel, which puts forward the assumption that the entire narrative of the novel is a confabulative.